Evidence for nodeless superconductivity in NdO1−xFxBiS2 (x = 0.3 and 0.5) single crystals. (19th May 2015) - Jiao, Lin; Weng, Zongfa; Liu, Jianzhong; Zhang, Jinglei; Pang, Guiming; Guo, Chunyu; Gao, Fei; Zhu, Xiyu; Wen, Hai-Hu; Yuan, H Q
Abstract: We study the superconducting pairing states of NdO1− x F x BiS2 ( x = 0.3 and 0.5) by measuring the magnetic penetration depth Δ λ ( T ) using the tunnel-diode-oscillator (TDO) technique. An upturn is observed in Δ λ ( T ) as well as the magnetic susceptibility χ ( T ) in the low-temperature limit, which is attributed to the paramagnetism of Nd ions. After subtracting the paramagnetic contributions, the penetration depth Δ λ ( T ) follows an exponential-type temperature dependence at T ≪ T c, providing evidence of nodeless superconductivity for NdO1− x F x BiS2 . This is further supported by the analyses of superfluid density ρ s ( T ), which can be well described by a BCS model with an energy gap of Δ(0) ∼ 2.15 k B T c .